Qualitative analysis of the boards of directors role in Russian companies: a number of in-depth interviews - Юлия Ивановна Дуляк (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
Authors: Julia Ivanovna Dulyak - National Research University "Higher School of Economics."This study examines the role and the place of the boards of directors in the activity of Russian public and nonpublic companies. The informational base of the paper – 15 in-depth interviews with the members of the boards and specialists in the field of corporate governance conducted in spring-summer 2012.